2010
DOI: 10.1029/2009ja014766
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity dependence of ion upflow in the polar ionosphere observed with the European Incoherent Scatter (EISCAT) Tromsø UHF radar

Abstract: The influence of solar activity upon ion upflow in the polar ionosphere was investigated using data obtained by the European Incoherent Scatter (EISCAT) Tromsø UHF radar between 1984 and 2008. In agreement with other work we find that the upward ion flux is generally higher when solar activity is high than when it is low. Ion upflow events and also the upward velocity behave the opposite: they are more frequently seen and higher, respectively, at times of low solar activity. In any year about 30–40% ion upflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 39 publications
3
41
2
Order By: Relevance
“…Therefore, the polar wind is typically dominated by hydrogen, and the bulk auroral ion upflow dominated by oxygen. In both cases, the observed ion velocity is on average larger and the ion flux lower at solar minimum than at solar maximum (Abe et al 2004;Ogawa et al 2010).…”
Section: Topside Ionospheric Ion Upflow and Accelerationmentioning
confidence: 85%
“…Therefore, the polar wind is typically dominated by hydrogen, and the bulk auroral ion upflow dominated by oxygen. In both cases, the observed ion velocity is on average larger and the ion flux lower at solar minimum than at solar maximum (Abe et al 2004;Ogawa et al 2010).…”
Section: Topside Ionospheric Ion Upflow and Accelerationmentioning
confidence: 85%
“…The effect of ion frictional heating is expected to increase with K P and to be stronger on the dusk side and in the winter: this explains the higher occurrence frequency on the dusk side at EISCAT's latitude, and the increase in occurrence frequency with geomagnetic activity at both ESR and EISCAT. The effect of soft electron precipitation is expected to be stronger during disturbed times, particularly in the dusk quadrant, and to play a more dominant role on the dayside where the precipitating electrons tend to be softer: this explains the higher Ogawa et al (2010) dayside occurrence frequency at ESR compared with EISCAT at both quiet and disturbed times, and the higher frequency on the dawn side during disturbed times. It also suggests that soft electron-driven electron heating may be more efficient than convection-driven ion heating in driving ion upflow.…”
Section: High Latitude Ionospheric Plasmamentioning
confidence: 90%
“…The apparent movement of the dayside ion upflow region may be understood in terms of the influence of solar wind velocity and density and the IMF B Y and B Z on the shape, size and location of the upflow region, since the location of the dayside cusp is known to move equatorward with decreasing IMF B Z or increasing solar wind dynamic pressure. Ogawa et al (2010) found the average starting altitude of ion up-flow to track the measured electron density peak and to be typically 100-150 km higher than the latter. The distribution of starting altitude is quite different at low and high solar flux, respectively.…”
Section: High Latitude Ionospheric Plasmamentioning
confidence: 99%
“…conditions correspond to solar minimum, and the higher upflow speeds are typical for periods of low Sun activity [Ogawa et al, 2010]. It is interesting that despite the high electron temperature, the ion temperature barely changes (see Figure 4e).…”
Section: Low-energy Precipitationmentioning
confidence: 93%